Wiki communities’ management tools in conditions of digitization - Kalinichenko, Lyudmila; Melnyk, Leonid; Kubatko, Oleksandr; Burlakova, Iryna; Babych, Kostiantyn; Pasko, Tatiana (Problems and perspectives in management, 2024)
The rise of local and global challenges (such as COVID-19, wars, natural disasters, etc.) requires advanced communication and information technologies to support economic development. The study aims to form a theoretical basis and practical tools for creating and functioning of wiki communities. Wiki communities are a new form of social association based on Internet communications of socio-economic subjects (individuals and organizations), in which each participant has equal rights to receive information, exchange opinions, and generate solutions. The theoretical basis involves substantiating the key principles on which wiki communities are formed, e.g., decentralization, openness, peering, sharing, and mass nature of activity. Wiki communities are represented by a set of specific types, such as professional, academic and research, custom, creative, public and non-commercial communities. The specific managing activities of wiki communities are described by several classification levels, such as operational activities, ensuring security, quality assurance, and motivation. The wiki community management toolkit includes a goal-setting algorithm, decision-making procedures, communications, rules of operation, typical tasks, areas of application, the operation and development cycle, and functional capabilities. It allows effective transfer of information, communication in real-time, and mutually enriching each other in forming knowledge and innovation. AcknowledgmentThe publication was prepared in the framework of the research project “Restructuring of the national economy in the direction of digital transformations for sustainable development” (№0122U001232) from National Research Foundation.